Strategic Management Deficiencies and Business Failure Among Private Medical Diagnostic Centers in Enugu, Nigeria - Marcellinus Chukwuka Ihionu; Alexander Chinaza Aneke (Universitas Pelita Harapan, 2026)
Private medical diagnostic centers play an increasingly important role in Nigeria’s healthcare delivery system, particularly in filling service gaps created by limited public health infrastructure. Despite their growing relevance, many of these facilities experience early business failures, especially in urban healthcare markets such as Enugu State. However, limited empirical attention has been given to the strategic and operational factors responsible for the collapse of private diagnostic laboratories in Nigeria. This study therefore examines the strategic management deficiencies associated with business failure among private medical diagnostic centers in Enugu State. The study adopted a historical case-based research approach, analyzing ten defunct diagnostic centers that operated between 2015 and 2025. Data were derived from archival reports, regulatory records, and secondary literature, and analyzed using qualitative content analysis. Findings reveal that business failure resulted from interconnected regulatory, operational, financial, and market-related challenges. Key factors included regulatory non-compliance, weak quality management systems, poor financial planning, high operational costs driven by energy and foreign exchange pressures, and increased competition within the healthcare market. The COVID-19 pandemic further exposed resilience gaps in many facilities. The study concludes that strengthening regulatory compliance, improving financial management practices, and adopting digital diagnostic technologies are essential for enhancing the sustainability of private diagnostic centers. The study contributes to healthcare entrepreneurship literature by providing a systems-based explanation of diagnostic facility failure in a developing economic context.